(untitled) (Scientific Researches in Academia, 2024)
Kathmandu, the capital of Nepal, faces significant traffic congestion due to rapid urban growth, impacting residents’ daily lives and hindering economic and environmental sustainability. This study investigates the global implementation of IoT in traffic management, drawing lessons for Kathmandu and identifying associated challenges. Using a mixed-methods approach, primary data were collected via surveys and interviews with traffic authorities, urban planners, and residents, while secondary data came from existing traffic reports and studies. The findings reveal positive perceptions of IoT’s role in traffic management, with high optimism for its effectiveness (Mean = 2.05) and low standard deviations indicating consensus. Significant correlations were found between IoT, smart infrastructure, public awareness, and traffic management. Regression analysis shows a strong model fit (R-squared = 0.759), highlighting the positive impact of public awareness and infrastructure on traffic management. However, caution is advised in generalizing the findings, and further research is recommended to explore additional factors influencing traffic management in Kathmandu.